Preventive and Therapeutic Effects of Epigallocatechin-3-Gallate (EGCG) on Collagen-Induced Arthritis in Rats. - Ozgen, Metin; Koca, Suleyman Serdar; Dagli, Adile Ferda; Karatas, Ahmet; Orhan, Cemal; Gencoglu, Hasan; Isik, Ahmet (Wiley, 2011)
[Abstract Not Available]
75th Annual Scientific Meeting of the American-College-of-Rheumatology (ACR) / 46th Annual Scientific Meeting of the Association-of-Rheumatology-Health-Professionals (ARHP) -- NOV 04-09, 2011 -- Chicago, IL